PENGEMBANGAN PERPUSTAKAAN DIGITAL BAGI TUNA NETRA MELALUI KERJASAMA LEMBAGA UNTUK MENDUKUNG TERCAPAINYA SDGS - Dwi Untari; Hariyah Hariyah; Noorika Retno Wulandari (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
Libraries have an important role in supporting the achievement of the SDGS 2030 agenda through providing access to information and knowledge to the blind. This study aimed to examine the development, obstacles and challenges of digital libraries and the forms of collaboration  that can be done for the development of digital libraries for the blind. This study used descriptive qualitative research methods. The results of this study show that Digital Library developed by Mitra Netra Foundation faces several obstacles, specifically the lack of collaboration with publishers  to increase the number of e-pub titles, the technology illiteracy of the blind, the difficulty in translating formulas such as in matematics by using screen reader, the lack of meaning of the novel and poetry read by the machine due to intonation and emotion inaccuracy,  and Mitra Netra Foundation limited budget to develop Digital Library. The challenges faced are how to improve the technology literacy of users and the blind, and increase the number of collections on the Digital Library page. To overcome these obstacle and challenges, public libraries, especially the national library an regional libraries may collaborate in providing tools to access Digital Library, conducting talking computer trainnings so that the blind become technology literate persons, promoting Digital Library and increasing the number of publications on the Digital Library page. In addition to public libraries, institutions or publishers can also collaboration in leading licenses  / copyright by providing soft copises of their works to the foundations to be converted into e-pub forms so that they can be accessed by the blind.